High-Molecular-Mass Multi-c-Heme Cytochromes from Methylococcus capsulatus Bath - Bergmann, David J. (American Society for Microbiology (ASM), 1999)
The polypeptide and structural gene for a high-molecular-mass c-type cytochrome, cytochrome c(553O), was isolated from the methanotroph Methylococcus capsulatus Bath. Cytochrome c(553O) is a homodimer with a subunit molecular mass of 124,350 Da and an isoelectric point of 6.0. The heme c concentration was estimated to be 8.2 ± 0.4 mol of heme c per subunit. The electron paramagnetic resonance spectrum showed the presence of multiple low spin, S = 1/2, hemes. A degenerate oligonucleotide probe synthesized based on the N-terminal amino acid sequence of cytochrome c(553O) was used to identify a DNA fragment from M. capsulatus Bath that contains occ, the gene encoding cytochrome c(553O). occ is part of a gene cluster which contains three other open reading frames (ORFs). ORF1 encodes a putative periplasmic c-type cytochrome with a molecular mass of 118,620 Da that shows approximately 40% amino acid sequence identity with occ and contains nine c-heme-binding motifs. ORF3 encodes a putative periplasmic c-type cytochrome with a molecular mass of 94,000 Da and contains seven c-heme-binding motifs but shows no sequence homology to occ or ORF1. ORF4 encodes a putative 11,100-Da protein. The four ORFs have no apparent similarity to any proteins in the GenBank database. The subunit molecular masses, arrangement and number of hemes, and amino acid sequences demonstrate that cytochrome c(553O) and the gene products of ORF1 and ORF3 constitute a new class of c-type cytochrome.